A durable PLA / plant fiber low-carbon composite material and preparation method thereof

By modifying biodegradable matrix resin and plant fiber through multi-layer surface treatment, combined with barrier and anti-degradation slow-release materials, the problem of easy decomposition of existing biodegradable materials has been solved, realizing high-strength, durable, low-carbon composite materials and broadening the application range.

CN115093667BActive Publication Date: 2025-01-10SHENZHEN WODAXUAN ENERGY SAVING & ENVIRONMENTAL PROTECTION IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210546273.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-20
Publication Date
2025-01-10
Estimated Expiration
2042-05-20

AI Technical Summary

Technical Problem

Existing biodegradable materials are easily decomposed under the influence of oxidation, photodegradation, microorganisms, and water vapor. They also lack thermal stability and physical strength, resulting in short service life and limited application range.

Method used

A durable PLA/plant fiber low-carbon composite material is made up of modified biodegradable matrix resin, modified plant fiber, modified composite diatomaceous earth, high-impact PA11/PETG elastomer, modified seaweed powder and crosslinking agent. The compatibility and bonding strength are improved through two-stage composite grafting technology and multi-layer surface treatment, and the degradation is delayed by the combination of barrier anti-degradation slow-release material.

Benefits of technology

This has resulted in high-strength, durable, low-carbon composite materials, extending service life, improving the thermal stability and physical strength of the materials, and broadening their application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, and relates to the technical field of polymer composite materials; the composite material is composed of: modified biodegradable base resin, 20-90 parts; modified plant fiber, 0-50 parts; modified composite diatomaceous earth, 1-5 parts; high-impact PA11 / PETG elastomer, 5-10 parts; modified seaweed powder, 0-6 parts; cross-linking agent, 1-5 parts; comprehensive auxiliary agent, 1-5 parts; the modified biodegradable base resin includes a first modified resin and a second modified resin; the first modified resin is PPC, and the second modified resin includes a resin modified from one or more of PBAT, PCL, PLA, PBS, PBSA, PBST, PHB, PHA, PVA, and PHBV; the production and preparation of a low-carbon composite material with high strength and durability is achieved while taking into account biodegradability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer composite materials, and in particular to a durable PLA / plant fiber low-carbon composite material and a preparation method thereof. Background Art

[0002] From the perspective of materials, we should vigorously promote the use of biodegradable plastics to replace traditional petroleum-based plastics on the one hand; on the other hand, we should make good use of agricultural and forestry waste and negative carbon materials. If we define petroleum-based plastics as "positive carbon materials (producing and emitting carbon dioxide)"; materials that consume or absorb carbon dioxide during the manufacturing process are called "negative carbon materials"; materials that do not emit or absorb carbon dioxide during the manufacturing process are called "zero carbon materials"; and the carbon footprint of plant-based or biodegradable plastics is usually only 50-70% of that of petroleum-based plastics, which can be called "green materials"; then materials with a carbon footprint between plant-based biodegradable materials and "zero carbon materials" can be called "low carbon materials".

[0003] On the other hand, the widespread use of petroleum-based plastics has spread across all walks of life and has even reached the point of flooding. In particular, the rise of online shopping and takeout has caused these non-degradable traditional petroleum-based plastics to form "white pollution" that damages the ecological environment, and further threatens and harms various organisms and even humans through the food chain. Therefore, promoting "green biodegradable polymers" has become the best solution to "plastic waste."

[0004] However, although there are corresponding biodegradable materials in the industry, there are still many problems, resulting in large application limitations of the materials; for example, the products are easily decomposed by oxidation, light degradation, microorganisms, and water vapor, and the service life is not long; the thermal stability and physical strength of the products are poor, resulting in limited application scope. Therefore, in order to provide a durable low-carbon composite material, it is necessary to overcome the above industry problems. Summary of the invention

[0005] The purpose of the present application is to provide a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, so as to realize the preparation of a low-carbon composite material with high strength and durability while taking into account biodegradability.

[0006] In order to achieve the above technical objectives, the present application provides a durable PLA / plant fiber low-carbon composite material and a preparation method thereof. In a first aspect, the present application provides a durable PLA / plant fiber low-carbon composite material: the composition of the composite material is:

[0007] Modified biodegradable base resin, 20-90 parts;

[0008] Modified plant fiber, 0-50 parts;

[0009] Modified composite diatomaceous earth, 1-5 parts;

[0010] High impact PA11 / PETG elastomer, 5-10 parts;

[0011] Modified seaweed powder, 0-6 parts;

[0012] Cross-linking agent, 1-5 parts;

[0013] Comprehensive additives, 1-5 parts;

[0014] The modified biodegradable base resin includes a first modified resin and a second modified resin;

[0015] The first modified resin is PPC (poly(methyl ethylene carbonate), and the second modified resin includes a resin modified from one or more of PBAT, PCL, PLA, PBS, PBSA, PBST, PHB, PHA, PVA, and PHBV.

[0016] Preferably, the modified biodegradable matrix resin consists of modified PPC, modified PLA and modified PBS.

[0017] Preferably, the ratio of the modified PPC, modified PLA and modified PBS in the composite material is

[0018] Modified PPC, 10-15 parts;

[0019] Modified PLA, 5-54 parts;

[0020] Modified PBS, 0-30 parts.

[0021] Preferably, the modification process of the modified biodegradable base resin comprises the following steps:

[0022] Solid phase grafting reaction: the modified biodegradable matrix resin is placed in a vacuum dryer for drying for 50-70 minutes, then the composite tourmaline additive and the grafting agent are added and irradiated with ultraviolet light, and then put into a high-speed mixer for mixing to obtain the biodegradable matrix resin after solid phase grafting;

[0023] Melt grafting reaction: the biodegradable matrix resin after solid phase grafting is respectively put into different high-speed mixers, and maleic anhydride and DCP are added for thorough mixing.

[0024] Preferably, in the solid phase grafting reaction step, the rotation speed of the high speed mixer is 1000-1300 rpm, and the mixing time is 25-35 minutes.

[0025] Preferably, the modification process of the modified plant fiber or modified seaweed powder comprises the following steps:

[0026] A1. Place the phytoplasma into a vacuum rotary heating dryer and stir and dry at 80-100°C for 1-2 hours;

[0027] A2. Introduce oxygen flow, turn on the ion source in the vacuum dryer, and perform plasma treatment for 3-6 minutes while stirring;

[0028] A3. First layer surface treatment: spray stearic acid and acetic anhydride under ultraviolet light, then irradiate with light for about 5-10 minutes while stirring;

[0029] A4. Second layer surface treatment: spray stearic acid coupling agent and stir for 3-5 minutes under UV light;

[0030] A5. The third layer of surface treatment: spray PVA aqueous solution and cross-linking agent, and stir for 3-5 minutes under ultraviolet light.

[0031] Preferably, the plant origin comprises one or more of bamboo fiber, wheat straw fiber, sisal fiber, kenaf fiber, rice straw fiber, rice husk powder or microalgae powder;

[0032] When there is more than one phytoplasma, the modification processes of different phytoplasmas are carried out separately.

[0033] Preferably, in step A3, the stearic acid coupling agent accounts for 1% of the mass of the phytoplasma; and the acetic anhydride accounts for 1% of the mass of the phytoplasma.

[0034] Preferably, the modification process of the modified composite diatomite comprises the following steps:

[0035] B1. Add halloysite, silane coupling agent, epoxy soybean oil and stearic acid into a high-speed mixer and stir and activate at high speed;

[0036] B2, further adding antioxidant 1010, antioxidant 168 and chitosan into the mixture obtained in step B2, stirring and mixing to obtain chitosan-intercalated halloysite;

[0037] B3, feeding the galactosan intercalated halloysite into a kneader, adding dopamine, PVA resin and diatomaceous earth, and kneading at 90-130° C. for 5-10 minutes;

[0038] B4. The mixed material in step B3 is put into a twin-screw granulator for extrusion granulation at 120-160°C.

[0039] Preferably, in step B1, the mass parts of the components are: 100 parts of halloysite, 1 part of silane coupling agent, 1 part of epoxy soybean oil, and 1 part of stearic acid;

[0040] In step B2, the mass fractions of the components are:

[0041] Antioxidant 1010, 10 parts; Antioxidant 168, 10 parts; Chitosan 30 parts;

[0042] In step B3, the mass fractions of the components are: 1 part of dopamine, 5 parts of PVA resin, and 300 parts of diatomaceous earth.

[0043] Preferably, the preparation of the high impact PA11 / PETG elastomer comprises the following steps:

[0044] C1. Mix PA11 with glycerol, formamide and benzenesulfonamide plasticizer in a high-speed mixer for 30-60 minutes, and then let it stand for use;

[0045] C2. Place PETG, epoxy chain extender (ADR4468), PPC and polyethylene glycol into another high-speed mixer and mix at high speed for 30-50 minutes;

[0046] C3, taking the mixture after standing in step C1 and mixing it with the mixture in step C2, and adding DCP (diisopropyl peroxide) and GMA (glycidyl methacrylate), and mixing for 10-15 minutes;

[0047] C4, putting the mixed material uniformly mixed in step C3 into a twin-screw extruder for volume expansion grafting reaction; the extrusion granulation temperature is 160-190° C. to obtain the high impact PA11 / PETG elastomer.

[0048] Preferably, in step C1, the proportions of the components are: PA11, 85%; glycerol, 3%; formamide, 2%; benzenesulfonamide plasticizer, 7%; the standing time is 6 hours;

[0049] In step C2, the proportions of the components are: PETG, 90%; epoxy chain extender (ADR4468), 1%; PPC, 5%; polyethylene glycol 4%;

[0050] In step C3, the ratio of the mixture of step C1 to the mixture of step C2 is 3:7, and the DCP and the GMA account for 0.1% and 3% of the mass of the mixture after mixing in step C3, respectively.

[0051] Preferably, the cross-linking agent is composed of ultrafine barium sulfate, water-repellent carbodiimide, and MDI (cross-linking agent diphenylmethane diisocyanate).

[0052] Preferably, the ratio of the components of the cross-linking agent is: ultrafine barium sulfate: water-repellent carbodiimide: MDI = 2:2:1.

[0053] Preferably, the comprehensive auxiliary agent consists of calcium stearate, PE wax and antioxidant 1010.

[0054] Preferably, the ratio of each component of the comprehensive auxiliary agent is: calcium stearate: PE wax: antioxidant 1010 = 4-6: 2-4: 1-3.

[0055] Preferably, the composite material comprises:

[0056] modified biodegradable base resin, 37 parts;

[0057] modified vegetable fibers, 46 parts;

[0058] Modified composite diatomaceous earth, 4 parts;

[0059] High impact PA11 / PETG elastomer, 8 parts;

[0060] Cross-linking agent, 3 parts;

[0061] Comprehensive additives, 2 parts.

[0062] In a second aspect, the present application provides a method for preparing a durable PLA / plant fiber low-carbon composite material, which is used to prepare any of the above-mentioned composite materials, comprising the following steps:

[0063] The components are put into a high-speed mixer according to a proportion and mixed, and the evenly mixed mixture is fed into a twin-screw extruder for micro-crosslinking reaction granulation, wherein the extrusion temperature is 160-190° C. to obtain the durable PLA / plant fiber low-carbon composite material.

[0064] Compared with the prior art, the beneficial effects of this application are:

[0065] (1) The modified biodegradable matrix resin is modified by a two-stage composite grafting technology, which improves the compatibility and bonding strength between biodegradable polymers or between them and other polymers (bio-based non-degradable materials or petroleum-based resins);

[0066] (2) Using plant fibers as raw materials to turn agricultural waste into treasure; and by modifying plant fibers and performing three-layer surface treatment, to overcome the compatibility problem of plant fibers in the industry;

[0067] (3) Two barrier and anti-degradation slow-release materials are used, and the long-term and short-term barrier and anti-degradation methods are used to effectively delay the degradation time of the composite material;

[0068] (4) Functional nanodiatomite loaded with halloysite nanotubes and chitosan is used as one of the barrier and anti-degradation sustained-release materials, which is safe and non-toxic, has good biocompatibility, excellent antibacterial effect and low cost;

[0069] (5) Plant-based PA / PETG high-impact elastomer is used as one of the barrier and anti-degradation sustained-release materials. It has high impact resistance, low water absorption, wear resistance, good adhesion, acid and alkali resistance, and excellent surface printability. At the same time, the elastomer has good compatibility with PPC and can accept a high filling amount of PPC. In addition, when using the elastomer, this scheme overcomes the problem of poor bonding between PETG and PA11 by modifying it, thereby realizing the production of the elastomer.

[0070] (6) During the preparation of the elastomer, dual-effect catalysis and dynamic cross-linking enable the nanoparticles in the alloy elastomer to have excellent dispersion and uniform active nodes. Various polymer chains are thus intertwined and entangled to form a stable network. Therefore, even if more than 30% of recycled resin is used, the final physical properties are still good.

[0071] (7) This scheme overcomes the production difficulties in the industry by achieving the preparation of a low-carbon composite material that is both biodegradable and high-strength and durable.

[0072] Chart Description

[0073] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the charts and graphs required for use in the embodiments or the description of the prior art are briefly introduced below.

[0074] Table 1 is a table of composition ratios of some embodiments;

[0075] Table 2 is a table of the composition ratios of some of the embodiments

[0076] Table 3 is a comparison table of physical property changes and weight loss rates of some examples;

[0077] Table 4 is a comparison table of physical property changes and weight loss rates of some examples;

[0078] Table 5 is a distribution table of initial tensile strength data of some embodiments;

[0079] Table 6 is a distribution table of initial impact strength data of some embodiments; DETAILED DESCRIPTION

[0080] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with embodiments. Several embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive:

[0081] The following describes in detail the durable PLA / plant fiber low-carbon composite material provided by the present invention and its preparation method:

[0082] Specifically, the present invention provides a durable PLA / plant fiber low-carbon composite material, which is composed of:

[0083] Modified biodegradable base resin, 20-90 parts;

[0084] Modified plant fiber, 0-50 parts;

[0085] Modified composite diatomaceous earth, 1-5 parts;

[0086] High impact PA11 / PETG elastomer, 5-10 parts;

[0087] Modified seaweed powder, 0-6 parts;

[0088] Cross-linking agent, 1-5 parts;

[0089] Comprehensive additives, 1-5 parts;

[0090] The modified biodegradable matrix resin includes a first modified resin and a second modified resin; the first modified resin is PPC, and the second modified resin includes a resin modified from one or more of PBAT, PCL, PLA, PBS, PBSA, PBST, PHB, PHA, PVA, and PHBV;

[0091] Furthermore, the modified biodegradable matrix resin is preferably composed of modified PPC (poly(methyl ethylene carbonate), modified PLA, and modified PBS;

[0092] Furthermore, modified PPC, modified PLA, modified PBS

[0093] The proportion in the composite material is:

[0094] Modified PPC, 10-15 parts;

[0095] Modified PLA, 5-54 parts;

[0096] Modified PBS, 0-30 parts.

[0097] Specifically, the modification process of the modified biodegradable base resin includes the following steps:

[0098] Solid phase grafting reaction: the modified biodegradable matrix resin is placed in a vacuum dryer for drying for 50-70 minutes, then the composite tourmaline additive and the grafting agent are added and irradiated with ultraviolet light, and then put into a high-speed mixer for mixing to obtain the biodegradable matrix resin after solid phase grafting;

[0099] Melt grafting reaction: the biodegradable matrix resin after solid phase grafting is put into different high-speed mixers, and maleic anhydride and DCP are added for thorough mixing;

[0100] Wherein, in the above modification process of the modified biodegradable matrix resin, the drying time is preferably 60 minutes;

[0101] Furthermore, in the solid phase grafting reaction step, the speed of the high speed mixer is 1000-1300 rpm, and the mixing time is 25-35 minutes.

[0102] Furthermore, in the solid phase grafting reaction, the mixing speed of the high-speed machine is preferably 1200 rpm, and the time is preferably 30 minutes;

[0103] Further, the proportion of maleic anhydride is 1%, and the proportion of DCP is 0.05%.

[0104] Specifically, the modification process of the modified plant fiber or modified seaweed powder includes the following steps:

[0105] A1. Place the phytoplasma into a vacuum rotary heating dryer and stir and dry at 85-100℃ for 1-2 hours;

[0106] A2. Introduce oxygen flow, turn on the ion source in the vacuum dryer, and perform plasma treatment for 3-6 minutes while stirring;

[0107] A3. First layer surface treatment: spray stearic acid and acetic anhydride under ultraviolet light, then irradiate with light for about 5-10 minutes while stirring;

[0108] A4. Second layer surface treatment: spray stearic acid coupling agent and stir for 3-5 minutes under UV light;

[0109] A5. The third layer of surface treatment: spray PVA aqueous solution and cross-linking agent, and stir for 3-5 minutes under ultraviolet light.

[0110] Further, the phytogenetics include one or more of bamboo fiber, wheat straw fiber, sisal fiber, kenaf fiber, rice straw fiber, rice husk powder or microalgae powder;

[0111] Wherein, when there is more than one phytoplasma, the modification processes of different phytoplasmas are carried out separately;

[0112] Furthermore, in step A3, the stearic acid coupling agent accounts for 1% of the mass of the phytoplasma; and the acetic anhydride accounts for 1% of the mass of the phytoplasma.

[0113] Furthermore, in step A5, the concentration of the PVA aqueous solution is preferably 5%; the cross-linking agent is preferably glyoxal, and the stirring time is preferably 5 minutes.

[0114] Specifically, the modification process of the modified composite diatomite includes the following steps:

[0115] B1. Add halloysite, silane coupling agent, epoxy soybean oil and stearic acid into a high-speed mixer and stir and activate at high speed;

[0116] B2, further adding antioxidant 1010, antioxidant 168 and chitosan into the mixture obtained in step B2, stirring and mixing to obtain chitosan-intercalated halloysite;

[0117] B3, feeding the galactosan intercalated halloysite into a kneader, adding dopamine, PVA resin and diatomaceous earth, and kneading at 90-130° C. for 5-10 minutes;

[0118] B4. The mixed material in step B3 is put into a twin-screw granulator for extrusion granulation at 120-160°C.

[0119] Further, in step B1, the mass parts of the components are: 100 parts of halloysite, 1 part of silane coupling agent, 1 part of epoxy soybean oil, and 1 part of stearic acid;

[0120] In step B2, the mass fractions of the components are:

[0121] Antioxidant 1010, 10 parts; Antioxidant 168, 10 parts; Chitosan 30 parts;

[0122] In step B3, the mass fractions of the components are: 1 part of dopamine, 5 parts of PVA resin, and 300 parts of diatomaceous earth.

[0123] Furthermore, the model of the silane coupling agent is KH570; in step B1, the stirring speed of the high-speed mixer is preferably 1000 rpm, and the stirring time is preferably 30 minutes.

[0124] Specifically, the preparation of high impact PA11 / PETG elastomer includes the following steps:

[0125] C1. Mix PA11 with glycerol, formamide and benzenesulfonamide plasticizer in a high-speed mixer for 30-60 minutes, and then let it stand for use;

[0126] C2. Place PETG, epoxy chain extender (ADR4468), PPC and polyethylene glycol into another high-speed mixer and mix at high speed for 30-50 minutes;

[0127] C3, taking the mixture after standing in step C1 and mixing it with the mixture in step C2, and adding DCP (diisopropyl peroxide) and GMA (glycidyl methacrylate), and mixing for 10-15 minutes;

[0128] C4, putting the mixed material uniformly mixed in step C3 into a twin-screw extruder for volume expansion grafting reaction; the extrusion granulation temperature is 160-190° C. to obtain the high impact PA11 / PETG elastomer.

[0129] Further, in step C1, the preferred proportions of the components are: PA11, 85%; glycerol, 3%; formamide, 2%; benzenesulfonamide plasticizer, 7%; the standing time is preferably 6 hours;

[0130] Further, in step C2, the proportions of the components are: PETG, 90%; epoxy chain extender (ADR4468), 1%; PPC, 5%; polyethylene glycol 4%;

[0131] Furthermore, in step C3, the ratio of the mixture of step C1 to the mixture of step C2 is 3:7, and the DCP and the GMA account for 0.1% and 3% of the mass of the mixture after mixing in step C3, respectively.

[0132] Specifically, the cross-linking agent is composed of ultrafine barium sulfate, water-repellent carbodiimide, and MDI (cross-linking agent diphenylmethane diisocyanate);

[0133] Furthermore, the ratio of each component of the cross-linking agent is preferably: superfine barium sulfate: water-repellent carbodiimide: MDI = 2:2:1.

[0134] Specifically, the comprehensive additives consist of calcium stearate, PE wax, and antioxidant 1010;

[0135] Furthermore, the ratio of each component of the comprehensive auxiliary agent is preferably: calcium stearate: PE wax: antioxidant 1010 = 4-6: 2-4: 1-3.

[0136] Furthermore, the composition of the composite material is preferably:

[0137] modified biodegradable base resin, 37 parts;

[0138] modified vegetable fibers, 46 parts;

[0139] Modified composite diatomaceous earth, 4 parts;

[0140] High impact PA11 / PETG elastomer, 8 parts;

[0141] Cross-linking agent, 3 parts;

[0142] Comprehensive additives, 2 parts.

[0143] The present invention also provides a method for preparing a durable PLA / plant fiber low-carbon composite material, comprising the following steps:

[0144] The components are mixed in a high-speed mixer according to the proportion, and the uniformly mixed mixture is fed into a twin-screw extruder for micro-crosslinking reaction granulation, wherein the extrusion temperature is 160-190° C., to obtain the durable PLA / plant fiber low-carbon composite material;

[0145] Furthermore, in the above method, the rotation speed of the screw is preferably 120 rpm.

[0146] The following will be further discussed from the specific embodiments:

[0147] Example 1

[0148] This embodiment provides a carbon biodegradable green composite material, which includes the following components:

[0149] X-PLA (54%) + X-PBS (29%) + X-PPC (15%) + comprehensive additives Mix (2%);

[0150] Among them, X-PLA, X-PBS, and X-PPC refer to modified PLA, modified PBS, and modified PPC, respectively, and MIX refers to comprehensive additives;

[0151] The preparation method is as follows:

[0152] (1) First, PLA, PBS, and PPC resins were placed in a rotary vacuum dryer for drying for 60 minutes, and then the composite tourmaline additive and grafting agent were added. The four UV lamps (total 100W) on the cover of the dryer were turned on, and high-speed mixing (1200 rpm) was performed for 30 minutes to complete the first stage of solid-phase grafting reaction;

[0153] (2) The above main raw materials (PLA, PBS, PPC after solid phase grafting) and additives are respectively put into three different high-speed mixers for thorough mixing;

[0154] a. PLA + 1% MAH (maleic anhydride) + 0.05% DCP;

[0155] b. PBS + 1% MAH (maleic anhydride) + 0.05% DCP;

[0156] c. PPC + 1% MAH (maleic anhydride) + 0.05% DCP;

[0157] After mixing for 15 minutes, the materials were fed into a kneader and then fed into a twin-screw extruder for melt grafting reaction and granulation to obtain three grafted resins, namely X-PLA, X-PBS, and X-PPC.

[0158] (3) The three grafted resins and the comprehensive additives (Mix) obtained above were mixed in a high-speed mixer according to the formula ratio (15 minutes), and then fed into a parallel twin-screw extruder for dynamic micro-crosslinking reaction (extrusion temperature of 160-180°C, screw speed of 120rpm), and granulated to obtain a low-carbon biodegradable green composite material.

[0159] This material is suitable for the production of injection molded parts. It has excellent physical strength and high surface activity. The injection molded parts are easy to spray with water-based paint or perform surface treatment to imitate metal appearance.

[0160] Comparative Example 1

[0161] This embodiment provides a carbon biodegradable green composite material, which includes the following components:

[0162] PLA (54%) + PBS (29%) + PPC (15%) + comprehensive additives Mix (2%);

[0163] The preparation method is as follows:

[0164] (1) Vacuum dehumidification and drying of resin:

[0165] First, PLA, PBS, and PPC resins were placed in a rotary vacuum dryer for 60 minutes;

[0166] (2) Put the above main raw materials (PLA, PBS, PPC) and 2% additives (Mix) into a high-speed mixer and mix them thoroughly;

[0167] (3) After mixing for 15 minutes, the material is fed into a kneader and then fed into a twin-screw extruder for melt extrusion granulation (extrusion temperature is 160-180°C, screw speed is 120rpm), and a low-carbon biodegradable green composite material is obtained.

[0168] Example 2

[0169] This embodiment provides a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, which comprises the following components:

[0170] X-PLA (35%) + X-PPC (10%) + t-rice straw fiber (20%) + t-rice husk powder (20%) + general diatomaceous earth (4%) + cross-linking agent CL (3%) + t-seaweed powder (6%) + comprehensive additive Mix (2%);

[0171] Among them, t-rice straw fiber is modified rice straw fiber, and the subsequent writing method refers to this explanation; CL is a cross-linking agent;

[0172] The preparation method is as follows:

[0173] (1) Modification of the biodegradable matrix resin: The modified biodegradable matrix resin is modified by a two-stage composite grafting method. The specific method can be referred to Example 1.

[0174] (2) Preparation of modified plant fibers

[0175] A1. Take rice straw fiber and rice husk powder and put them into a vacuum rotary heating dryer, stir and dry them at 80-100℃ for 1-2 hours;

[0176] A2. Then, introduce oxygen gas flow, turn on the ion source in the vacuum dryer, and perform plasma treatment for 3-6 minutes while stirring.

[0177] A3. After plasma treatment, turn on the UV light source inside the upper cover of the machine, spray stearic acid (1% of the fiber weight) and acetic anhydride (1% of the fiber weight), and then irradiate for about 5-10 minutes while stirring. This is the first layer of surface treatment.

[0178] A4, then spray stearic acid coupling agent (accounting for 1% of the total weight of the fiber), stir and expose to UV light for 3-5 minutes, this is the second layer of surface treatment;

[0179] A5. Finally, spray PVA aqueous solution (concentration 5%) and cross-linking agent (glyoxal), stir and expose to UV light for 5 minutes. This is the third layer of surface treatment.

[0180] (3) The components prepared above are put into a high-speed mixer for mixing according to the formula (mix at low speed for 3 minutes, switch to high speed mixing for 5 minutes, and then mix at low speed for 3 minutes); finally, the mixed ingredients are fed into a twin-screw extruder for micro-crosslinking reaction granulation (extrusion temperature is 160-190°C, screw speed is 120rpm).

[0181] Comparative Example 2

[0182] This embodiment provides a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, which comprises the following components:

[0183] X-PLA (35%) + X-PPC (10%) + general rice straw fiber (20%) + general rice husk powder (20%) + general diatomaceous earth (4%) + cross-linking agent CL (3%) + general seaweed powder (6%) + comprehensive additive Mix (2%);

[0184] The preparation method is as follows:

[0185] (1) The modified biodegradable matrix resin is modified by a two-stage grafting method. The specific method can be referred to Example 1;

[0186] (2) Take rice straw fiber and rice husk powder and put them into a vacuum rotary heating dryer respectively, and stir and dry them at 80-100 degrees C for 1-2 hours;

[0187] (3) The components prepared above are put into a high-speed mixer for mixing according to the formula (mix at low speed for 3 minutes, switch to high speed mixing for 5 minutes, and then mix at low speed for 3 minutes); finally, the mixed ingredients are fed into a twin-screw extruder for micro-crosslinking reaction granulation (extrusion temperature is 160-190°C, screw speed is 120rpm).

[0188] Example 3

[0189] This embodiment provides a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, which comprises the following components:

[0190] X-PLA (22%) + X-PPC (10%) + X-PBS (5%) + t-rice straw fiber (20%) + t-rice husk powder (20%) + high impact PA11 / PETG elastomer (8%) + modified diatomaceous earth (HINs-CD) (4%) + cross-linking agent CL (3%) + t-seaweed powder (6%) + comprehensive additive Mix (2%);

[0191] The preparation method is as follows:

[0192] (1) The modified biodegradable matrix resin is modified by a two-stage grafting method. The specific method can be referred to Example 1;

[0193] (2) Preparing modified plant fibers. The specific method can be referred to Example 2;

[0194] (3) Preparation of modified diatomite

[0195] B1. Place 100 parts of halloysite in a high-speed mixer, add 1 part of silane coupling agent (KH570), 1 part of epoxidized soybean oil (EBO), and 1 part of stearic acid; then start high-speed stirring (1000 rpm) for 30 minutes to activate it;

[0196] B2, then add 10 parts of antioxidant 1010, 10 parts of antioxidant 168 and 30 parts of chitosan, and mix for 15-30 minutes to complete the chitosan intercalation halloysite;

[0197] B3. The chitosan intercalated halloysite in step B2 is fed into a kneader, and 1 part of dopamine, 5 parts of PVA resin and 300 parts of diatomaceous earth are added. Mix at 90-130 degrees C for 5-10 minutes;

[0198] B4. The mixed material in step B3 is put into a twin-screw granulator for modified granulation of diatomaceous earth; the extrusion temperature of the granulator is 120-160°C.

[0199] (4) Preparation of high impact PA11 / PETG elastomer

[0200] C1. Mix 85% PA11 with 3% glycerol, 2% formamide, and 7% benzenesulfonamide plasticizer in a high-speed mixer for 30-60 minutes, and then let it stand for 6 hours;

[0201] C2. Place 90% PETG, 1% epoxy chain extender, 5% PPC, and 4% polyethylene glycol (PEG2000) in another high-speed mixer and mix at high speed for 30 minutes.

[0202] C3. Take 30 kg of the mixture in step C1 after standing for 6 hours, pour it into 70 kg of the mixture in step C2 (a total of 100 kg), then add 0.1% DCP and 3% GMA, and mix for 10 minutes.

[0203] C4, feeding the uniformly mixed material in step C3 into a twin-screw extruder for volume expansion grafting reaction. The extrusion granulation temperature is 160-190° C., thus obtaining a high-impact PA11 / PETG alloy elastomer.

[0204] (5) The components prepared above are put into a high-speed mixer for mixing according to the formula (mix at low speed for 3 minutes, switch to high speed mixing for 5 minutes, and then mix at low speed for 3 minutes); finally, the mixed ingredients are fed into a twin-screw extruder for micro-crosslinking reaction granulation (extrusion temperature is 160-190°C, screw speed is 120rpm).

[0205] Example 4

[0206] This embodiment provides a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, which comprises the following components:

[0207] X-PLA (22%) + X-PPC (10%) + X-PBS (5%) + t-bamboo fiber (40%) + high impact PA11 / PETG elastomer (8%) + modified diatomaceous earth (4%) + cross-linking agent (3%) + t-seaweed powder (6%) + comprehensive additive Mix (2%);

[0208] The preparation method is as follows:

[0209] (1) The modified biodegradable matrix resin is modified by a two-stage grafting method. The specific method can be referred to Example 1;

[0210] (2) Preparing modified plant fibers. The specific method can be referred to Example 2;

[0211] (3) preparing modified diatomaceous earth, the specific method can refer to Example 3;

[0212] (4) Preparation of high impact PA11 / PETG elastomer, the specific method can refer to Example 3;

[0213] (5) The components prepared above are put into a high-speed mixer for mixing according to the formula (mix at low speed for 3 minutes, switch to high speed mixing for 5 minutes, and then mix at low speed for 3 minutes); finally, the mixed ingredients are fed into a twin-screw extruder for micro-crosslinking reaction granulation (extrusion temperature is 160-190°C, screw speed is 120rpm).

[0214] Example 5

[0215] This embodiment provides a durable PLA / plant fiber low-carbon composite material and a preparation method thereof, which comprises the following components:

[0216] X-PLA (5%) + X-PPC (10%) + X-PBS (15%) + t-rice straw fiber (20%) + t-rice husk powder (20%) + t-bamboo fiber (7%) + high impact PA11 / PETG elastomer (8%) + modified diatomaceous earth (HINs-CD) (4%) + cross-linking agent CL (3%) + t-seaweed powder (6%) + comprehensive additive Mix (2%);

[0217] (1) The modified biodegradable matrix resin is modified by a two-stage grafting method. The specific method can be referred to Example 1;

[0218] (2) Preparing modified plant fibers. The specific method can be referred to Example 2;

[0219] (3) preparing modified diatomaceous earth, the specific method can refer to Example 3;

[0220] (4) Preparation of high impact PA11 / PETG elastomer, the specific method can refer to Example 3;

[0221] (5) The components prepared above are put into a high-speed mixer for mixing according to the formula (mix at low speed for 3 minutes, switch to high speed mixing for 5 minutes, and then mix at low speed for 3 minutes); finally, the mixed ingredients are fed into a twin-screw extruder for micro-crosslinking reaction granulation (extrusion temperature is 160-190°C, screw speed is 120rpm).

[0222] In the technical solution provided by the present invention, polypropylene carbonate (PPC) is used, which is a biodegradable material. Although PPC is non-toxic, tasteless, and a completely degradable material with good barrier properties, it actually has low mechanical properties, poor thermal properties, large brittleness, narrow processing temperature range, and poor compatibility with other polymers (PLA, PBS, PBAT, PCL, etc.). Therefore, PPC must be modified before it can be effectively used; therefore, the modified biodegradable matrix resin is modified by a two-stage composite grafting method;

[0223] Furthermore, the present invention also focuses on controlling the cost of raw materials, while taking into account waste utilization, adhering to the purpose of green environmental protection, so some plant fibers are used as one of the raw materials, and the properties of plant fibers are used to enhance the composite material proposed by the present invention, but the compatibility between the biodegradable matrix resin and the plant fibers is also a major problem, so this solution performs three surface treatments on the plant fibers and also modifies the plant fibers;

[0224] Furthermore, conventional biodegradable materials generally have the problem of service life, and there is no better solution; the present invention uses direct (quick release) and indirect (long-term sustained release) delay and barrier means to make the biodegradable polymer have excellent properties such as high efficiency anti-hydrolysis, anti-aging, anti-gas permeation, and anti-cracking, thereby greatly improving the durability, thereby making it have a wider range of applications;

[0225] Furthermore, the first barrier anti-degradation sustained-release material used in the present invention is modified diatomite, and further is functional nano-diatomite loaded with halloysite nanotubes and chitosan; wherein, the present invention utilizes halloysite nanotubes as a natural nanoclay in nature, which is a natural one-dimensional nanotube, and its inner and outer surfaces have many active hydroxy acids, so it is easy to carry out surface modification or introduce functional groups. Furthermore, the present invention further considers that it is safe and non-toxic, has good biocompatibility, and is low in cost. Compared with various other nanotubes such as carbon nanotubes and boron nitride, halloysite nanotubes have a higher cost performance; in addition, chitosan is selected to utilize it as a Natural degradable polymers are not only biocompatible but also have antibacterial effects. Diatomaceous earth can not only improve heat resistance and mechanical strength, but also make the surface of the material smooth (reduce surface bumps and floating fibers) and make it easier to print. In this way, the composite material provided by the present invention can combine its characteristics. However, it is not easy to prepare modified diatomaceous earth by combining the above-mentioned materials. In this scheme, the halloysite nanotubes are first modified and activated, and antioxidants and anti-hydrolysis agents are connected. Then, the shell fungicide is intercalated once by the dense mixing method, and finally the intercalated material and the modified diatomaceous earth (PVA modified) are intercalated by a second melt extrusion using a cross-linking agent.

[0226] Furthermore, the second barrier anti-degradation sustained-release material used in the present invention is a high-impact PA11 / PETG elastomer. PETG (polyethylene terephthalate-1,4-cyclohexanedimethanol) is a copolymer resin of PET. It has high transparency, good toughness, good weather resistance, and is easy to process. It is a recognized environmentally friendly material. The present invention selects PETG and plant-based nylon PA11 to blend and cross-link to form an elastomer that resists fatigue cracking, which has the following advantages:

[0227] (1) High impact resistance, (2) Low water absorption, (3) Wear resistance, (4) Good adhesion, (5) Acid and alkali resistance, (6) Excellent surface printability; Another feature is that this elastomer is very compatible with PPC and can accept a high filling amount of PPC; However, the bonding strength between PETG and PA11 is not good, and it is not easy to achieve a comprehensive application of the two. For this reason, the scheme further adopts the scheme of grafting GMA after PA11 softens, and then reacting with PETG for chain extension, and finally melt co-extruding into a compatible high-impact elastomer.

[0228] Furthermore, this solution uses dual-effect catalysis and dynamic cross-linking to achieve excellent dispersion of nanoparticles in the alloy elastomer and to form uniform active nodes. Various polymer chains are thus intertwined and entangled to form a stable network. Therefore, even if more than 30% of recycled resin is used, the final physical properties are still good.

[0229] The following is a further analysis of the final experimental results of each embodiment:

[0230] Specifically referring to FIG. 3 , comparing the control example 1 with the embodiment 1, the weight loss rate of the embodiment 1 is greatly different from the weight loss rate of the control example 1. Therefore, it can be concluded that the present invention significantly prolongs the service life in practical application by modifying the biodegradable base resin.

[0231] Specifically referring to Figure 4, comparing Control Example 2 and Example 2, it can be seen that the various parameters in Example 2 are significantly better than those in Control Example 2, whether in terms of tensile strength, elongation at break or the final weight loss rate, there are large differences between the two. This shows that this solution effectively improves the bonding force between plants and polymers by further activating and grafting plant fibers, thereby significantly improving the various physical properties of the material.

[0232] Further referring to Figure 4, comparing Examples 3-5 with Control Example 2, after adding two slow-release anti-degradation barriers to Examples 3-5, the physical properties of the composite materials are further improved. Specifically, the weight loss rates of Example 4 and Control Example 2 can be compared. Among them, the weight loss rate of the control example after 30 days is -53.6%, while the weight loss rate of Example 4 after 30 days is only -14.3%, which is more than twice the difference, which is very significant in extending the service life of the material.

[0233] Further, please refer to Figures 5-6. By conducting this experiment on the materials and comparing the stability of the materials, and comparing with Control Example 2, Example 2 and Example 4, it can be obtained from the results of multiple experiments that Implementation 2 and Example 4 are not only better than Control Example 2 in terms of original data, but also better than Control Example 2 in terms of stability, which further proves that the two types of "multi-stage post-grafting" in this scheme make the bonding force between the resin and the plant fiber very uniform and stable in the present application.

[0234] Table 1

[0235]

[0236] Table 2

[0237]

[0238] Table 3

[0239]

[0240] Table 4

[0241]

[0242] Table 5

[0243]

[0244] Table 6

[0245]

[0246] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.

[0247] The above description is only a preferred embodiment of the present application and does not constitute any form of limitation to the present application. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application are within the scope of the technical solution of the present application.

Claims

1. A durable PLA / plant fiber low-carbon composite material, characterized by: The composition of the composite material is: Modified biodegradable base resin, 20-90 parts; Modified plant fiber, 0-50 parts; Modified composite diatomaceous earth, 1-5 parts; High impact PA11 / PETG elastomer, 5-10 parts; Modified seaweed powder, 0-6 parts Cross-linking agent, 1-5 parts; Comprehensive additives, 1-5 parts; The modified biodegradable base resin includes a first modified resin and a second modified resin; The first modified resin is PPC (poly(methyl ethylene carbonate)), and the second modified resin includes a resin modified from one or more of PBAT, PCL, PLA, PBS, PBSA, PBST, PHB, PHA, PVA, and PHBV; The modification process of the modified biodegradable matrix resin comprises the following steps: Solid phase grafting reaction: the modified biodegradable matrix resin is placed in a vacuum dryer for drying for 50-70 minutes, then the composite tourmaline additive and the grafting agent are added and irradiated with ultraviolet light, and then put into a high-speed mixer for mixing to obtain the biodegradable matrix resin after solid phase grafting; Melt grafting reaction: the biodegradable matrix resin after solid phase grafting is put into different high-speed mixers, and maleic anhydride and DCP are added for thorough mixing; The modification process of the modified plant fiber or modified seaweed powder comprises the following steps: A1. Place the phytosol in a vacuum rotary heating dryer and dry at 80-100°C for 1-2 hours; A2. Introduce oxygen flow, turn on the ion source in the vacuum dryer, and perform plasma treatment for 3-6 minutes while stirring; A3. First layer surface treatment: spray stearic acid and acetic anhydride under ultraviolet light, then irradiate with light for 5-10 minutes while stirring; A4. Second layer surface treatment: spray stearic acid coupling agent and stir for 3-5 minutes under UV light; A5. Third layer surface treatment: spray PVA aqueous solution and cross-linking agent, stir for 3-5 minutes under UV light; The modification process of the modified composite diatomite comprises the following steps: B1. Add halloysite, silane coupling agent, epoxy soybean oil and stearic acid into a high-speed mixer and stir and activate at high speed; B2, further adding antioxidant 1010, antioxidant 168 and chitosan into the mixture obtained in step B1, stirring and mixing to obtain chitosan intercalated halloysite; B3, feeding the chitosan intercalated halloysite into a kneader, adding dopamine, PVA resin and diatomaceous earth, and kneading at 90-130° C. for 5-10 minutes; B4. The mixed material in step B3 is put into a twin-screw granulator for extrusion granulation at 120-160°C.

2. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: The modified biodegradable matrix resin consists of modified PPC, modified PLA and modified PBS.

3. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: In the solid phase grafting reaction step, the rotation speed of the high speed mixer is 1000-1300 rpm, and the mixing time is 25-35 minutes.

4. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: The phytoproma comprises one or more of bamboo fiber, wheat straw fiber, sisal fiber, kenaf fiber, rice straw fiber, rice husk powder or microalgae powder; When there is more than one phytoplasma, the modification processes of different phytoplasmas are carried out separately.

5. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: In step A3, the stearic acid coupling agent accounts for 1% of the mass of the phytoplasma; and the acetic anhydride accounts for 1% of the mass of the phytoplasma.

6. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: In step B1, the mass parts of the components are: 100 parts of halloysite, 1 part of silane coupling agent, 1 part of epoxy soybean oil, and 1 part of stearic acid; In step B2, the mass fractions of the components are: Antioxidant 1010, 10 parts; Antioxidant 168, 10 parts; Chitosan 30 parts; In step B3, the mass fractions of the components are: 1 part of dopamine, 5 parts of PVA resin, and 300 parts of diatomaceous earth.

7. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: The preparation of the high impact PA11 / PETG elastomer comprises the following steps: C1. Mix PA11 with glycerol, formamide and benzenesulfonamide plasticizer in a high-speed mixer for 30-60 minutes, and then let it stand for use; C2. Place PETG, epoxy chain extender, PPC and polyethylene glycol in another high-speed mixer and mix at high speed for 30-50 minutes; C3, taking the mixture after standing in step C1 and mixing it with the mixture in step C2, and adding DCP (dicumyl peroxide) and GMA (glycidyl methacrylate), and mixing for 10-15 minutes; C4, putting the mixed material uniformly mixed in step C3 into a twin-screw extruder for volume expansion grafting reaction; the extrusion granulation temperature is 160-190° C. to obtain the high impact PA11 / PETG elastomer.

8. The durable PLA / plant fiber low-carbon composite material according to claim 7, characterized in that: The cross-linking agent is composed of superfine barium sulfate, water-repellent carbodiimide, and MDI (cross-linking agent diphenylmethane diisocyanate).

9. The durable PLA / plant fiber low-carbon composite material according to claim 8, characterized in that: The ratio of the components of the cross-linking agent is: superfine barium sulfate: water-repellent carbodiimide: MDI=2:2:

1.

10. The durable PLA / plant fiber low-carbon composite material according to claim 1, characterized in that: The comprehensive auxiliary agent consists of calcium stearate, PE wax and antioxidant 1010.

11. The durable PLA / plant fiber low-carbon composite material according to claim 10, characterized in that: The proportions of the components of the comprehensive auxiliary agent are: calcium stearate: PE wax: antioxidant 1010 = 4-6: 2-4: 1-3.

12. The durable PLA / plant fiber low-carbon composite material according to any one of claims 1 to 11, characterized in that: The composition of the composite material is: modified biodegradable base resin, 37 parts; modified vegetable fibers, 46 parts; Modified composite diatomaceous earth, 4 parts; High impact PA11 / PETG elastomer, 8 parts; Cross-linking agent, 3 parts; Comprehensive additives, 2 parts.

13. A method for preparing a durable PLA / plant fiber low-carbon composite material, characterized in that: The method for preparing the durable PLA / plant fiber low-carbon composite material according to any one of claims 1 to 12 comprises the following steps: The components are put into a high-speed mixer according to a proportion and mixed, and the evenly mixed mixture is fed into a twin-screw extruder for micro-crosslinking reaction granulation, wherein the extrusion temperature is 160-190° C. to obtain the durable PLA / plant fiber low-carbon composite material.

Citation Information

Patent Citations

  • High-toughness full-degradable composite material

    CN110655769A

  • Bamboo-based fiber reinforced full-biodegradable composite material

    CN112980158A